Pengaruh Infrastruktur Riset dan Kolaborasi Riset Terhadap Pengembangan PLTS di Desa Pematang Johar Kecamatan Labuhan Deli Kabupaten Deli Serdang - Siregar, Mahdalena Waty (Inovasi, 2024)
This research aims to analyze the influence of research infrastructure and research collaboration on the development of Solar Power Plants (PLTS) in Pematang Johar Village, Labuhan Deli District, Deli Serdang Regency. This research uses a quantitative approach with survey methods to collect data from stakeholders involved in PLTS development, including researchers, project managers and village communities. The type of research used is qualitative research with an associative explanatory research model. SuThe research objects are the community and related institutions in the Pematang Johar Village Environment, Kec. Labuhan Deli District. Deli Serdang, North Sumatra Province, while the research object is variables that influence each other, both dependent variables and independent variables, these variables include Research Infrastructure, Research Collaboration and PLTS Development. The population in this research is the community and related institutions in the Pematang Johar Village Environment, Kec. Labuhan Deli District. Deli Serdang.The sample determined based on the survey was 120 (one hundred and twenty) people/participants. Considering that the members of the population are homogeneous, the author took 100% so that the total number was 120 (one hundred and twenty) respondents. The research results show that:1) there is an influence of the Research Infrastructure Variable (X1) on PLTS Development (Y) of 0.337; 2) there is an influence of Research Collaboration (X2) on PLTS Development (Y) of 0.570; and 3) there is an influence of Research Infrastructure (X1) and Research Collaboration (X2) on PLTS Development (Y) of 0.660, so that the influence of PLTS Development on other variables is obtained by an e value of 0.340. Key words: research infrastructure, research collaboration, solar power plant, Pematang Johar, Indonesia